2021
DOI: 10.1002/jcp.30627
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis: A possible link between obesity‐related inflammation and inflammatory diseases

Abstract: The main manifestation of obesity is persistent low‐level inflammation and insulin resistance, which is an important factor inducing or promoting other obesity‐related diseases. As a proinflammatory programmed cell death, pyroptosis plays an important role, especially in the activation and regulation of the NLRP3 inflammasome pathway. Pyroptosis is associated with the pathogenesis of many chronic inflammatory diseases and is characterized by the formation of micropores in the plasma membrane and the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 160 publications
(202 reference statements)
0
11
0
Order By: Relevance
“…In recent years, pyroptosis has become a hot topic of research. As the signaling pathways regulating mechanisms are gradually elucidated, researchers have also found that pyroptosis plays a considerable role in many human diseases and has important implications for disease treatment [ 51 ]. However, the molecular mechanism of regulating the expression of GSDMD in cold stress has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, pyroptosis has become a hot topic of research. As the signaling pathways regulating mechanisms are gradually elucidated, researchers have also found that pyroptosis plays a considerable role in many human diseases and has important implications for disease treatment [ 51 ]. However, the molecular mechanism of regulating the expression of GSDMD in cold stress has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This can be regarded as a limitation of the current study. Since the discovery of GSDMD as the first key protein involved in pyroptosis through the classical NLRP3–caspase-1 axis, other gasdermins, including gasdermins B, C, and E, have been discovered along with the noncanonical pyroptosis pathway involving caspase-11/4/5 [ 50 ]. The existence of other types of gasdermins shows the complexity of the pyroptosis pathway and implies that deficiency in one factor could easily be compensated by other factors.…”
Section: Discussionmentioning
confidence: 99%
“…ER pathway has also been involved in tumorigenesis and promote protumor TME particularly in hormone-sensitive tumors such as breast, ovarian, endometrial, and prostate ( 55 ). Inflammasome activation by activated fatty acids and high glucose levels observed in obesity, which has been linked to breast cancer and colorectal cancer, has also been acknowledged for obesity-associated cancer development ( 56 , 57 ). NLRP3 inflammasome activation induced by E2 can also trigger pyroptosis and inhibit autophagy in HCC cells ( 58 ).…”
Section: Discussionmentioning
confidence: 99%